A Research on Reading Therapy of Chinese University Students with Depression - Hua, Yang (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
This paper discusses the treatment of Chinese university students with depression by reading therapy, and provides theoretical and experimental basis for improving university students' depression. In this study, Beck Depression Inventory was used to measure the psychology of university students to discover depressed university students and evaluate the effect of reading therapy experiment. The researcher observed the effect of reading professional psychological books and general recreational books on university students' depression, and compared the two kinds of effects. Reading therapy has a significant effect on improving the psychological problems of Chinese university students with depression. General recreational reading is more effective in the treatment of university students depression than professional psychological reading.